PEREMPUAN MUSLIM DAN KETAHANAN EKONOMI KELUARGA: Studi di Kalangan Pelaku Pernikahan Dini di Jetis Karangrayung Grobogan - Muzdalifah, Muzdalifah; Syukur, M. Amin; Elizabeth, Misbah Zulfa (UIN Sunan Kudus, 2021)
A common phenomenon among perpetrators of early marriages is the fragility of the marriage structure due to their lack of readiness to lead family life. This doesnot happen in Jetis village. Karangrayung District, Grobogan Regency. Applying qualitative research, with the technique of data collecting observation, interview and document review, this study resulted that ; 1). Moslem women view that early married life is very difficult both psychologically and economically. However, women in the village have the initiative to maintain their marriage; 2). efforts made by women are trying to solve economic problems, namely by living a simple life, working hard, saving and doing entrepreneurship; 3). The reason women make various efforts is because of religious motives so that they are able to survive in a crisis or difficulty, so that they are able to rise again in maintaining the family economy, so that a prosperous and noble life can be achieved.